Consociationalism as a Minimal Benchmark for Normative Theory - Semenov, Andrej A.; Nedeljković, Zoran D. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This article argues that consociationalism, an instrument for managing deeply divided societies, can also be understood as a form of minimal normative political theory. Drawing on Arend Lijphart’s consociational model of democracy and juxtaposing it with the heavyweight theoretical models of John Rawls and Jürgen Habermas, the article presents the model not merely as a functional compromise but as a morally grounded framework suited to contexts of deep pluralism and mistrust. Lijphart’s consociational model is a morally grounded framework founded on three principles: coexistence without resolution (pluralism), peace as a precondition for justice, and institutional design as a moral choice. In this light, the model can serve as a minimal benchmark of what counts as a normative theory.